Byzantine Epitaphs Unearthing New Sources of Christian Socioreligious Landscape from Southeastern Al-Karak Plateau (Southern Jordan) - Al-Rawahneh, Musallam R. (2025)
The objective of this article is to bring to light seven previously unpublished Byzantine funerary inscriptions discovered in the southeastern Al-Karak Plateau (southeastern Moab, Jordan). These inscriptions are currently preserved in the Al-Karak Archaeological Museum in southern Jordan. Fortunately, most of these inscriptions are in relatively good condition, and the scripts correspond to types 2, 3, and 4 of the Canova classification. The inscriptions bear a striking resemblance to the many epitaphs from the fifth through seventh centuries CE carved on rectangular tombstones and adorned with Christian symbols in the same region.